Prevalence and mortality of ceftazidime/avibactam-resistant KPC-producing Klebsiella pneumoniae bloodstream infections (2018–2022) - Boattini, Matteo (2023)
Funding Information: Open access funding provided by Università degli Studi di Torino within the CRUI-CARE Agreement. This research was supported by EU funding within the MUR PNRR Extended Partnership initiative on Emerging Infectious Diseases (Project no. PE00000007, INF-ACT). Publisher Copyright: © 2023, The Author(s).